2001
DOI: 10.1097/00001573-200111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and hypertension

Abstract: Epidemiologic studies have consistently revealed inverse associations between physical activity (or fitness) and hypertension. There are hypotensive benefits to exercise training found across a number of aerobic and progressive resistance training modalities. Optimal exercise prescriptions remain unclear, but hypotensive benefits have been noted for mild to vigorous ranges of exercise intensity, for as few as three exercise sessions per week and durations as short as 20 minutes. Hypertensive subjects appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 26 publications
1
31
0
4
Order By: Relevance
“…The beneficial effect of physical exercise on arterial hypertension is mainly related to shear stress that is a potent stimulus to produce nitric oxide (NO) leading to vasodilatation. [3][4][5][6]7 Epidemiological studies have shown a strong association between erectile dysfunction and arterial hypertension. 8,9 However, the underlying mechanisms by which arterial hypertension is associated with erectile dysfunction are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of physical exercise on arterial hypertension is mainly related to shear stress that is a potent stimulus to produce nitric oxide (NO) leading to vasodilatation. [3][4][5][6]7 Epidemiological studies have shown a strong association between erectile dysfunction and arterial hypertension. 8,9 However, the underlying mechanisms by which arterial hypertension is associated with erectile dysfunction are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação ao TNF, todas as diretrizes citam maior efetividade com as medidas de redução do peso, restrição de sódio, prática regular de atividade física e consumo moderado de álcool [10][11][12][13][14][15] . Diversos estudos demonstram o papel da atividade física na redução da pressão arterial e da morbimortalidade cardiovascular 16-23 e vários são os mecanismos envolvidos no efeito hipotensor do treinamento físico, que se torna mais evidente a partir da décima semana de treinamento com pequenos ganhos adicionais subseqüentes [24][25][26][27] . A atividade física deve ser avaliada e prescrita em termos de intensidade, freqüência, duração, modo e progressão.…”
unclassified
“…Estudos epidemiológicos têm consistentemente revelado relação inversa entre atividade física (ou exercício) e a hipertensão arterial (PA), ou seja, o treinamento físico reduz significativamente a PA em pacientes com hipertensão arterial sistêmica (Lesniak, Dubbert, 2001). A alteração na função endotelial mediada pela redução da biodisponibilidade de NO está associada à hipertensão e a prática do exercício aeróbio tem demonstrado melhora na função endotelial em modelos animais hipertensos e em pacientes humanos com hipertensão essencial (Higashi, Yoshizumi, 2004).…”
Section: Discussionunclassified